On the discursive construction of the multiple meanings of francophonie/francophone viewed through the prism of argumentative semantics - Cozma, Ana-Maria (Kalbotyra, 2021)
This paper addresses the issue of polysemy, and more precisely of multiple meanings in the case of the words francophonie/francophone from the perspective of argumentative semantics. The aim of the paper is to examine the mechanisms that account for the multiple meanings of francophonie/francophone, i.e. the semantic and discursive mechanisms involved in the (re)construction of lexical meaning as the words occur in discourse. The data analysed in this paper consists of a set of discourse fragments about francophone identity, discourses that vary according to the speaker, the geographical location and the media support. The study is carried out within the framework of the SAP theory (Semantics of Argumentative Possibilities), following a procedure based on a pre-built reference meaning – i.e. a description of the argumentative potential of the lexeme – that will be used when analysing the discursive occurrences. First, the paper briefly presents the SAP theory and the pre-built reference meaning of the lexemes francophonie/francophone (described in terms of core-elements, stereotypes and argumentative possibilities). It then illustrates several discursive mechanisms of meaning construction. The analysis highlights a series of meaning construction mechanisms: transgressive activation of the argumentative potential, reconfiguration by scission of the core-elements or by deletion of one of the elements, modality addition, transgressive reconstruction of the core meaning, and finally core circularity. Thus, the paper indicates, from the perspective of argumentative semantics, that the multiple meanings of the words francophonie/francophone, i.e. the various semantic configurations attached to these words, can be seen as reconfigurations of a single lexical meaning.
Keywords: polysemy; multiple meanings; meaning construction; argumentative orientation; Semantics of Argumentative Possibilities; Galatanu; francophonia